Maintaining the integrity of XML signatures by using the manifest element - Hussain, Omar; Soh, B. (IEEE Industrial Electronics Society, 2004)
One of the aims of providing 'security of data' in e-commerce transactions is making sure that the receiver receives the same data which the sender sends, that is the data has not been tampered in any way. To achieve this aim digital signatures are used. A digital signature helps in providing integrity, message authentication, and signer authentication for the signed data. An XML signature can contain or point to the data that is being signed. In this paper we discuss a possible solution of avoiding a signature from breaking when there is a change in the location of the document after it has been signed.